A Critical Examination of Research Ethics in the Treatment Recommendations for Diarrhoea - Etaoghene Paul Polo; Shamima Parvin Lasker (Bangladesh Journal of Bioethics)
Primarily, this article emphasises that while conducting research, especially one involving human subjects, researchers are expected to comply with applicable global and national ethical standards. Should a researcher fail to do so, he/she stands the risk of breaching research ethics, and this is capable of rendering his/her research unacceptable. Accordingly, this article, making reference to relevant ethical theories, critically examines and analyses the actions of a researcher who set out to investigate treatment recommendations for diarrhoea. Ultimately, a number of ethical pitfalls in the stated research are x-rayed and some recommendations for subsequent studies are provided in this paper.